2010
DOI: 10.1111/j.1600-0609.2010.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of congenital dyserythropoietic anemias in Europe

Abstract: Congenital dyserythropoietic anemia (CDA) was first described in 1967. Soon after the first reports, it became evident that different types exist (1), which share ineffective erythropoiesis as the main mechanism of the anemia and which are all characterized by morphological abnormalities of the erythroblasts, but which are of distinct phenotype and genotype. Specific diagnostic data were first reported from indigenous populations and from AbstractCongenital dyserythropoietic anemias (CDAs) are rare hereditary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…13 The wide variation in CDA incidence among European regions could be due to genetic reasons and also to the presence of reference centers with advanced diagnostic procedures available for the diagnosis of CDAs. 10 The true frequency of CDA types I and II is most probably higher than that estimated. This could be due to clinical heterogeneity and diagnostic difficulties, as demonstrated by the observation that in these congenital diseases the correct diagnosis is often delayed until adulthood.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 82%
See 1 more Smart Citation
“…13 The wide variation in CDA incidence among European regions could be due to genetic reasons and also to the presence of reference centers with advanced diagnostic procedures available for the diagnosis of CDAs. 10 The true frequency of CDA types I and II is most probably higher than that estimated. This could be due to clinical heterogeneity and diagnostic difficulties, as demonstrated by the observation that in these congenital diseases the correct diagnosis is often delayed until adulthood.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 82%
“…Furthermore, in many families there is only one single affected individual, which makes determination of the inheritance pattern very difficult. Indeed recessive inheritance, de novo mutation and low expression alleles are difficult 10,15 Although CDA II patients are to be found right across the Italian peninsula, the majority of ancestors came from Southern Italy, where a founder effect has been observed. 13 The wide variation in CDA incidence among European regions could be due to genetic reasons and also to the presence of reference centers with advanced diagnostic procedures available for the diagnosis of CDAs.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most widely documented subtype of CDA, with approximately 367 cases reported in the literature, predominantly in European populations [15]. The term HEMPAS derives from observations by Crookston et al that the red blood cells from CDA II patients demonstrated susceptibility to lysis in ABO-compatible normal sera in the acidified serum lysis test (HAM's test) [16].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CDAs in Europe has been recently assessed [52]. After this evaluation, CDA II seems to be the most frequent form of CDAs.…”
Section: Hematological Disordersmentioning
confidence: 99%